Comparison of Antibiotics and Symptomatic Treatment for Uncomplicated Urinary Tract Infections - Muhammad Salman, Salman Khan, Kynat Rehman, Sanan Khan, Paras Yousuf, Murad Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The most frequent bacterial illness among patients who seek primary care is an uncomplicated urinary tract infection (UTI), which is also the leading cause of the rapidly growing strains of bacteria that are resistant to the developing antibiotic sector. The only approach is to employ antibiotics when direly necessary. This study was aimed to evaluate the efficacy of symptomatic therapy with antibiotics in adults with uncomplicated urinary tract infections. Methodology: This descriptive comparative study was carried out at Medical Unit of DHQ Teaching Hospital, Dera Ismail Khan for the duration from August 2022 to January 2023. A total of 140 adult patients in the age range of 20 to 70 years with urinary tracts infection in the absence of any complication were registered. UTI was confirmed based clinical symptoms of painful and frequent micturition, lower abdominal discomfort and fever supported by urinalysis showing more than 10 white cells/HPF and casts. Patients were arbitrarily assigned to two groups (A and B) in equal number. Patients in Group A received symptomatic management with antipyretics and pain killers while group B received antibiotics for 07 days. Treatment goal was subsidence of symptomatology measured on day 7 after treatment initiation. IBM SPSS version 25 was used for data analysis. Results: Age of the patients ranged from 20 to 70 years with mean age 31.40±5.411 years in symptomatic group versus 34.16±4.786 years in antibiotic group. Majority of the participants belong to age group 20-40 years in either treatment category. Female participants were more frequently registered in either treatment group. Symptomatic treatment was effective in 39 patients (55.7%) patients while antibiotics were effective in 63 patients (90.0%) patients (p value <0.001). Conclusion: Symptomatic treatment is not inferior to antibiotic treatment when proper patient selection is undertaken, resulting in decreased need for unnecessary antibiotics use. Keywords: Uncomplicated Urinary Tract Infection, Symptomatic Treatment, Antibiotic Treatment